Topographical and meteorological features of the arid region - Waters, Fred Dorsey (My University, 1898)
Introduction: This subject will be considered under two principal heads. 1st It’s the topography; and 2nd the meteorology of the arid region. First let us consider its topography. It would probably be best to give its boundaries and dimensions first in order that its extent and size may be well in mind. It is included between the 100 degree, and the 124 degree of west longitude, and north, and south between the 43 degree and the 27 degree of latitude. In other words it includes the western half of Kansas, Nebraska, the Dakotas, and the whole of California, Wyoming, New Mexico, Idaho, Utah, Arizona, and one third of Washington. Not including Alaska it amounts to about one third of the United States. Its greatest width from East to West is about 1300 miles, and from north to south, 1000 miles considering it as a whole, we find that topographically it divides itself naturally into three grand divisions, which though not arbitrary may be used in describing its general topographical features.
Citation: Waters, Fred Dorsey. Topographical and meteorological features of the arid region. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Topographical Features; Meteorological Features; Nature; Theses; Manuscripts (documents)